The Distribution and Abundance of Gastropods and Bivalves on The Coast of Kecinan, Pemenang, North Lombok: - Candri, Dining Aidil; Gusti Ngurah Eka Putra; Yuliadi Zamroni (Jurnal Moluska Indonesia, 2025)
Gastropods and Bivalves are important organisms to study in terms of community because they can serve as indicators of environmental quality due to their sedentary nature. This research was conducted in April 2024 at Kecinan Beach, Malaka, Pemenang District, North Lombok Regency, with the aim of identifying species and analyzing the distribution patterns and abudance of Gastropods and Bivalves in the intertidal zone. Sampling was conducted using the quadrat transect method in three observation areas, each divided based on different activities. In each area, a 50 meter transect was laid out toward the sea with 1 x 1 meter quadrats placed every 5 meters. Data were analyzed to obtain values for abundance, diversity index, dominance index, morisita index and evenness index. The results identified 131 species with 338 individuals, consisting of 107 species of Gastropods and 24 species of Bivalves. Stations I and II, which have good seagrass and coral reef ecosystems, showed a higher number of individuals  compared to station III, which is located near a river mouth. The diversity index at stations II and I was classified as high, while station III had a moderate index. The evenness index at all stations showed a stable distribution pattern. The low dominance index indicated that no species dominated the area.